Hydrophobic antifouling modified PVC film and preparation process thereof

CN122878684APending Publication Date: 2026-10-09NINGBO TRUE MATERIAL TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610915844.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

针对现有技术的不足,本发明提供了一种疏水防污改性PVC薄膜及其制备工艺,解决了PVC薄膜疏水、防污功能差的问题

Benefits of technology

(1)本发明中使用γ-(甲基丙烯酰氧基)丙基三甲氧基硅烷、1H,1H,2H,2H-全氟癸基三乙氧基硅烷对纳米二氧化硅进行改性,在纳米二氧化硅表面引入烯基和全氟硅烷,得到改性二氧化硅。以改性二氧化硅作为功能填料,加入到PVC树脂基体中,与助剂协同作用,制备得到改性PVC膜。改性二氧化硅能够在PVC基体中均匀分散,有效改善无机填料与有机树脂的界面相容性,改善了PVC薄膜表面能高、易吸附灰尘的缺陷,同时还能够起到物理补强作用,显著提升薄膜整体拉伸强度与断裂伸长率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of PVC films, and particularly discloses a hydrophobic and antifouling modified PVC film and a preparation process thereof. The hydrophobic and antifouling modified PVC film comprises a modified PVC film and a hydrophobic and antifouling coating. The raw materials of the modified PVC film comprise 100 parts of PVC resin, 5-12 parts of modified silicon dioxide, 20-35 parts of a composite plasticizer, 3-8 parts of a heat stabilizer, 1-4 parts of a lubricant and 1-3 parts of an antioxidant. The hydrophobic and antifouling coating is obtained by coating a hydrophobic and antifouling coating material on the modified PVC film. The raw materials of the hydrophobic and antifouling coating material comprise 40-60 parts of a hydrophobic and antifouling emulsion, 0.5-2 parts of a defoaming agent, 0.1-0.3 parts of a leveling agent and 1-3 parts of a thickening agent. The modified system is combined by the internal hydrophobic modification of the base body and the surface functional coating modification. Through the synergistic effect, the organic fluorosilicon low-surface-energy effect and the inorganic filler micro-roughness synergistic effect are effectively exerted, and the prepared modified PVC film has excellent and durable hydrophobic and antifouling performances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of PVC film technology, specifically to a hydrophobic and antifouling modified PVC film and its preparation process. Background Technology

[0002] PVC film is a polymer film material made from polyvinyl chloride resin as the main raw material, with the addition of auxiliary materials through processes such as mixing and molding. PVC film is inexpensive, has excellent processing performance, and excellent mechanical properties, making it widely used in architectural membrane structures, packaging materials, and agricultural films. However, the PVC molecular chain contains a large number of polar chlorine atoms, resulting in high surface energy. During long-term exposure to the external environment, dust, oil, microorganisms in the air, and pollutants in rainwater easily adhere to the film surface, forming dirt that is difficult to clean, severely affecting the appearance, service life, and application range of the PVC film.

[0003] Currently, various hydrophobic and antifouling PVC films have been proposed in existing technologies, but all have varying degrees of defects. Chinese patent application CN111777782A discloses a hydrophobic self-cleaning PVC film and its preparation method. It involves preparing a nano-silica hydrogel, mixing it with PVC to obtain a nano-slurry, spraying it onto the surface of a PVC base film, and then pressing it with a roller coated with micron-sized bumps to form a micro-roughened surface, imparting hydrophobicity and effectively preventing contaminants from adhering to the film, thus exhibiting self-cleaning properties. However, this method relies solely on surface physical roughness to improve hydrophobicity without chemically modifying the nano-silica, resulting in poor compatibility, easy aggregation, and precipitation with long-term use. The improvement in hydrophobic effect is limited, and the micron-sized bump roller lacks sufficient precision in controlling the nanostructure, easily causing structural inhomogeneity. Chinese patent application CN117362864A discloses an antibacterial PVC film with self-cleaning function. This antibacterial PVC film comprises PVC, fluorocarbon resin, deionized water, self-cleaning coating, polysiloxane, anatase nano-titanium dioxide, porous quartz powder, titanium tetrachloride, titanium nitrate, water-based curing agent, ultraviolet absorber, and chain extender. It has good self-cleaning, waterproof, anti-sticking, anti-fouling, wear-resistant, and antibacterial functions, but the raw materials have poor compatibility, easily leading to agglomeration and delamination defects. Chinese patent application CN107502176A discloses an anti-oil adhesive and a method for preparing an anti-oil, hydrophobic, high-strength PVC film using it. The anti-oil adhesive is composed of resin and fluorine- or silicone organic compounds. The anti-oil adhesive is applied to the surface of the PVC film using a coating machine, and after curing the anti-oil adhesive coating, an anti-oil, hydrophobic, high-strength PVC film is obtained, exhibiting anti-oil and hydrophobic effects. However, the coating has poor compatibility with the PVC film, weak adhesion, and is prone to peeling, resulting in poor durability.

[0004] Therefore, developing a modified PVC film with excellent hydrophobic and antifouling properties has become a pressing technical challenge in this field. Summary of the Invention

[0005] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides a hydrophobic and antifouling modified PVC film and its preparation process, which solves the problem of poor hydrophobic and antifouling properties of PVC films.

[0006] (II) Technical Solution To achieve the above objectives, the present invention discloses a hydrophobic and antifouling modified PVC film, comprising a modified PVC film and a hydrophobic and antifouling coating. The modified PVC film, by weight, comprises: 100 parts PVC resin, 5-12 parts modified silica, 20-35 parts composite plasticizer, 3-8 parts heat stabilizer, 1-4 parts lubricant, and 1-3 parts antioxidant. The hydrophobic and antifouling coating is obtained by applying a hydrophobic and antifouling paint onto a modified PVC film; The raw materials of the hydrophobic and antifouling coating, by weight, include: 40-60 parts of hydrophobic and antifouling emulsion, 0.5-2 parts of defoamer, 0.1-0.3 parts of leveling agent, and 1-3 parts of thickener.

[0007] Preferably, the modified PVC film is prepared by the following steps: A1. Nano silica, 90wt% ethanol solution, γ-(methacryloyloxy)propyltrimethoxysilane, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane were ultrasonically dispersed evenly. The pH of the solution was adjusted to 5 with glacial acetic acid, and the mixture was heated to allow the reaction to occur. After the reaction was completed, the mixture was centrifuged, washed with anhydrous ethanol, and dried to obtain modified silica. A2. Weigh out the PVC resin, modified silica, composite plasticizer, heat stabilizer, lubricant, and antioxidant by weight, and mix them evenly in a high-speed mixer at a speed of 300-400 r / min for 15-25 min to obtain a mixture. Add the mixture to a twin-screw extruder for melt blending, extrusion granulation, and obtain modified PVC granules. Add the granules to a calender for calendering, cooling and setting to obtain a modified PVC film.

[0008] Preferably, the mass ratio of nano-silica, 90wt% ethanol solution, γ-(methacryloyloxy)propyltrimethoxysilane, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane in A1 is 100:2400-2600:15-21:20-30, the reaction temperature is 75-85℃, and the reaction time is 18-24h.

[0009] Preferably, in the melt blending process of A2, the screw speed is 100-120 r / min, the melt blending temperature is 160-180℃, the melt blending time is 8-10 min, the calendering temperature is 180-200℃, and the calendering thickness is 0.1-0.3 mm.

[0010] Preferably, the preparation method of the hydrophobic and antifouling coating includes the following steps: B1. Zinc nitrate hexahydrate, halloysite nanotubes, and deionized water were ultrasonically dispersed evenly in a mass ratio of 200-600:100:8000-9500. Ammonia was added to adjust the pH to 9-10. The mixture was heated and reacted at 55-65℃ for 2 hours. After the reaction was completed, the mixture was centrifuged and washed with deionized water and anhydrous ethanol until neutral. It was then vacuum dried in a drying oven at 60℃ for 6 hours and calcined in a muffle furnace at 450-480℃ for 2-3 hours. After cooling, the nano-zinc oxide / haloysite nanotube composite filler was obtained. B2. Mix nano zinc oxide / haloite nanotube composite material, anhydrous ethanol, and γ-methacryloyloxypropyltrimethoxysilane in a mass ratio of 100:3200-3500:18-25 until homogeneous. Heat the mixture, stir, adjust the pH to 5-6 with hydrochloric acid solution, and react at 65-75℃ for 12-18 hours. After the reaction is complete, filter the mixture, wash it with deionized water and anhydrous ethanol, and dry it to obtain alkenyl-modified composite filler. B3. Deionized water, emulsifier, alkenyl modified composite filler, methyl methacrylate, tridecyl fluorooctyl methacrylate, and vinyltriethoxysilane are stirred and mixed. An initiator is added, and the reaction takes place in a nitrogen atmosphere. After the reaction is completed, the mixture is cooled and sieved to obtain a hydrophobic and antifouling emulsion. B4. Mix the hydrophobic and antifouling emulsion, defoamer, and leveling agent at a speed of 300-500 r / min for 10-15 min. Add the thickener and stir for 15-25 min. Let it stand and mature for 30-60 min. Sieve to obtain the hydrophobic and antifouling coating.

[0011] Preferably, the mass ratio of deionized water, emulsifier, alkenyl modified composite filler, methyl methacrylate, tridecyl fluorooctyl methacrylate, vinyltriethoxysilane, and initiator in B3 is 450-480:3-6:7-12:35-55:12-16:4-7:0.5-1, the reaction temperature is 70-75℃, and the reaction time is 6-8h.

[0012] Preferably, the emulsifier in B3 is sodium dodecyl sulfate.

[0013] Preferably, the initiator in B3 is ammonium persulfate.

[0014] Preferably, the composite plasticizer is composed of dibutyl phthalate and dioctyl phthalate in a mass ratio of 2:3; the heat stabilizer is a calcium-zinc composite heat stabilizer; the lubricant is butyl stearate; the antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the defoamer is an organosilicon defoamer; the leveling agent is a polyether-modified polysiloxane; and the thickener is a polyurethane thickener.

[0015] A method for preparing the hydrophobic and antifouling modified PVC film includes the following steps: Step 1: Perform surface plasma treatment on the modified PVC film, and then apply a hydrophobic and antifouling coating to the surface of the treated modified PVC film. Step 2: Place the coated modified PVC film in an oven for curing, cooling, and winding to obtain a hydrophobic and antifouling modified PVC film.

[0016] Preferably, in the plasma treatment process of step one, the treatment power is 80-100W, the treatment time is 3-5min, and the coating thickness is 10-16μm.

[0017] Preferably, the curing in step two is a three-stage curing process: the first stage is cured at 65-75℃ for 2-4 minutes, the second stage is cured at 85-100℃ for 4-6 minutes, and the third stage is cured at 105-115℃ for 2-4 minutes.

[0018] (iii) Beneficial technical effects Compared with the prior art, the beneficial effects of the present invention are as follows: (1) In this invention, γ-(methacryloyloxy)propyltrimethoxysilane and 1H,1H,2H,2H-perfluorodecyltriethoxysilane are used to modify nano-silica, introducing alkenyl groups and perfluorosilanes onto the surface of nano-silica to obtain modified silica. Modified silica is then used as a functional filler and added to a PVC resin matrix, working synergistically with additives to prepare a modified PVC film. The modified silica can be uniformly dispersed in the PVC matrix, effectively improving the interfacial compatibility between inorganic fillers and organic resins, improving the defects of high surface energy and easy dust adsorption in PVC films, and also playing a physical reinforcing role, significantly improving the overall tensile strength and elongation at break of the film.

[0019] (2) In this invention, zinc nitrate hexahydrate is used as the zinc source and combined with halloysite nanotubes to obtain a nano zinc oxide / haloysite nanotube composite filler. The nano zinc oxide / haloysite nanotube composite filler is modified with γ-methacryloyloxypropyltrimethoxysilane and copolymerized with fluorinated acrylic monomers and silane functional monomers to obtain a hydrophobic and antifouling emulsion. This emulsion is then mixed with additives to obtain a hydrophobic and antifouling coating. Nano zinc oxide has excellent aging resistance and UV resistance, while halloysite nanotubes have a porous structure. The composite filler, synergistically with fluorinated acrylic monomers and silane functional monomers, can form a dense and stable micro-rough fluorosilicone hydrophobic structure on the surface of the modified PVC film, giving the coating excellent hydrophobic and antifouling properties, and enabling surface self-cleaning.

[0020] (3) The present invention first uses plasma to activate the surface of the modified PVC film, which can effectively etch the film surface and introduce polar active groups, greatly improving the wettability and interfacial bonding between the PVC substrate and the hydrophobic and antifouling coating, and avoiding problems such as peeling, flaking and cracking of the coating. Furthermore, with the three-stage gradient temperature curing process, the coating can be slowly formed and fully cross-linked and cured, effectively eliminating the internal stress of the coating, and further improving the adhesion of the coating and the stability of the film.

[0021] (4) This invention combines internal hydrophobic modification of the matrix with surface functional coating composite modification. Through synergistic effect, it effectively leverages the low surface energy effect of organic fluorine silicon and the micro-roughness enhancement effect of inorganic fillers. The resulting modified PVC film has excellent hydrophobic and antifouling properties and can be widely used in packaging, decoration, building materials, daily films and other easily soiled application scenarios, with a wide range of applications. Detailed Implementation

[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0023] Example 1 A modified PVC film, the preparation method of which includes the following steps: A1. Nano silica, 90wt% ethanol solution, γ-(methacryloyloxy)propyltrimethoxysilane, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane were ultrasonically dispersed in a mass ratio of 100:2400:15:20. The pH of the solution was adjusted to 5 with glacial acetic acid, and the mixture was heated to 75℃ for 24 h. After the reaction was completed, the mixture was centrifuged, washed with anhydrous ethanol, and dried to obtain modified silica. A2. Weigh out 100 parts by weight of PVC resin, 5 parts by weight of modified silica, 20 parts by weight of composite plasticizer, 3 parts by weight of heat stabilizer, 1 part by weight of lubricant, and 1 part by weight of antioxidant. The composite plasticizer consists of dibutyl phthalate and dioctyl phthalate in a 2:3 mass ratio. The heat stabilizer is a calcium-zinc composite heat stabilizer. The lubricant is butyl stearate. The antioxidant consists of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio. Mix them evenly in a high-speed mixer. The mixing speed in the machine is 300 r / min, the mixing time is 25 min, and the resulting mixture is added to a twin-screw extruder for melt blending. During melt blending, the screw speed is 100 r / min, the melt blending temperature is 160℃, and the melt blending time is 10 min. The mixture is then extruded and granulated to obtain modified PVC granules, which are then added to a calender for calendering at a temperature of 180℃ and a calendering thickness of 0.3 mm. After cooling and setting, a modified PVC film is obtained.

[0024] Example 2 A modified PVC film, the preparation method of which includes the following steps: A1. Nano silica, 90wt% ethanol solution, γ-(methacryloyloxy)propyltrimethoxysilane, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane were ultrasonically dispersed in a mass ratio of 100:2500:18:25. The pH of the solution was adjusted to 5 with glacial acetic acid, and the mixture was heated to 80℃ for 21 h. After the reaction was completed, the mixture was centrifuged, washed with anhydrous ethanol, and dried to obtain modified silica. A2. Weigh out 100 parts by weight of PVC resin, 8 parts by weight of modified silica, 25 parts by weight of composite plasticizer, 5 parts by weight of heat stabilizer, 3 parts by weight of lubricant, and 2 parts by weight of antioxidant. The composite plasticizer consists of dibutyl phthalate and dioctyl phthalate in a 2:3 mass ratio; the heat stabilizer is a calcium-zinc composite heat stabilizer; the lubricant is butyl stearate; and the antioxidant consists of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio. Mix them evenly in a high-speed mixer. The feeder rotates at 350 r / min and mixes for 20 min to obtain a mixture. This mixture is then fed into a twin-screw extruder for melt blending. During melt blending, the screw speed is 110 r / min, the melt blending temperature is 170℃, and the melt blending time is 9 min. The mixture is then extruded and granulated to obtain modified PVC granules. These granules are then fed into a calender for calendering at 190℃ to a thickness of 0.2 mm. After cooling and setting, a modified PVC film is obtained.

[0025] Example 3 A modified PVC film, the preparation method of which includes the following steps: A1. Nano silica, 90wt% ethanol solution, γ-(methacryloyloxy)propyltrimethoxysilane, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane were ultrasonically dispersed in a mass ratio of 100:2600:21:30. The pH of the solution was adjusted to 5 with glacial acetic acid, and the mixture was heated to react at 85℃ for 18 h. After the reaction was completed, the mixture was centrifuged, washed with anhydrous ethanol, and dried to obtain modified silica. A2. Weigh out 100 parts by weight of PVC resin, 12 parts by weight of modified silica, 35 parts by weight of composite plasticizer, 8 parts by weight of heat stabilizer, 4 parts by weight of lubricant, and 3 parts by weight of antioxidant. The composite plasticizer consists of dibutyl phthalate and dioctyl phthalate in a 2:3 mass ratio; the heat stabilizer is a calcium-zinc composite heat stabilizer; the lubricant is butyl stearate; and the antioxidant consists of antioxidant 1010 and antioxidant 168 in a 1:1 mass ratio. Mix them evenly in a high-speed mixer. The feeder rotates at 400 r / min and mixes for 15 min to obtain a mixture. This mixture is then fed into a twin-screw extruder for melt blending. During melt blending, the screw speed is 120 r / min, the melt blending temperature is 180℃, and the melt blending time is 8 min. The mixture is then extruded and granulated to obtain modified PVC granules. These granules are then fed into a calender for calendering at 200℃ to a thickness of 0.1 mm. After cooling and setting, a modified PVC film is obtained.

[0026] Example 4 A method for preparing a hydrophobic and antifouling coating includes the following steps: B1. Zinc nitrate hexahydrate, halloysite nanotubes, and deionized water were ultrasonically dispersed in a mass ratio of 200:100:8000. Ammonia was added to adjust the pH to 9. The mixture was heated and reacted at 55°C for 2 hours. After the reaction was completed, the mixture was centrifuged and washed with deionized water and anhydrous ethanol until neutral. It was then vacuum dried in a drying oven at 60°C for 6 hours and calcined in a muffle furnace at 450°C for 3 hours. After cooling, nano-zinc oxide / haloysite nanotube composite filler was obtained. B2. A nano zinc oxide / haloite nanotube composite material with a mass ratio of 100:3200:18, anhydrous ethanol, and γ-methacryloyloxypropyltrimethoxysilane were mixed evenly, heated, stirred and mixed, and the pH was adjusted to 5 with hydrochloric acid solution. The mixture was reacted at 65°C for 18 hours. After the reaction was completed, the mixture was filtered, washed with deionized water and anhydrous ethanol, and dried to obtain an alkenyl-modified composite filler. B3. Deionized water, sodium dodecyl sulfate emulsifier, alkenyl modified composite filler, methyl methacrylate, tridecyl fluorooctyl methacrylate, and vinyltriethoxysilane are stirred and mixed. Ammonium persulfate initiator is added. The mass ratio of deionized water, emulsifier, alkenyl modified composite filler, methyl methacrylate, tridecyl fluorooctyl methacrylate, vinyltriethoxysilane, and initiator is 450:3:7:35:12:4:0.5. The reaction takes place in a nitrogen atmosphere at a temperature of 70°C for 8 hours. After the reaction is completed, the mixture is cooled and sieved to obtain a hydrophobic and antifouling emulsion. B4. By weight, mix 40 parts of hydrophobic and antifouling emulsion, 0.5 parts of defoamer, and 0.1 parts of leveling agent at 300 rpm for 15 minutes. Add 1 part of thickener, wherein the defoamer is an organosilicon defoamer, the leveling agent is a polyether-modified polysiloxane, and the thickener is a polyurethane thickener. Stir for 15 minutes, let stand for 30 minutes to mature, and sieve to obtain the hydrophobic and antifouling coating.

[0027] Example 5 A method for preparing a hydrophobic and antifouling coating includes the following steps: B1. Zinc nitrate hexahydrate, halloysite nanotubes, and deionized water were ultrasonically dispersed in a mass ratio of 400:100:9000. Ammonia was added to adjust the pH to 9.5. The mixture was heated to 60℃ and reacted for 2 hours. After the reaction was completed, the mixture was centrifuged and washed with deionized water and anhydrous ethanol until neutral. It was then vacuum dried in a drying oven at 60℃ for 6 hours and calcined in a muffle furnace at 460℃ for 2.5 hours. After cooling, the nano-zinc oxide / haloysite nanotube composite filler was obtained. B2. A nano-zinc oxide / haloite nanotube composite material with a mass ratio of 100:3400:21, anhydrous ethanol, and γ-methacryloyloxypropyltrimethoxysilane were mixed evenly, heated, stirred and mixed, and the pH was adjusted to 5.5 with hydrochloric acid solution. The mixture was reacted at 70°C for 14 hours. After the reaction was completed, the mixture was filtered, washed with deionized water and anhydrous ethanol, and dried to obtain an alkenyl-modified composite filler. B3. Deionized water, sodium dodecyl sulfate emulsifier, alkenyl modified composite filler, methyl methacrylate, tridecyl fluorooctyl methacrylate, and vinyltriethoxysilane are stirred and mixed. Ammonium persulfate initiator is added. The mass ratio of deionized water, emulsifier, alkenyl modified composite filler, methyl methacrylate, tridecyl fluorooctyl methacrylate, vinyltriethoxysilane, and initiator is 460:5:10:45:14:6:0.8. The reaction takes place in a nitrogen atmosphere at a temperature of 72°C for 7 hours. After the reaction is completed, the mixture is cooled and sieved to obtain a hydrophobic and antifouling emulsion. B4. By weight, mix 50 parts of hydrophobic and antifouling emulsion, 1.2 parts of defoamer, and 0.2 parts of leveling agent at 400 rpm for 12 minutes. Add 2 parts of thickener, wherein the defoamer is an organosilicon defoamer, the leveling agent is a polyether-modified polysiloxane, and the thickener is a polyurethane thickener. Stir for 21 minutes, let stand for 50 minutes to mature, and sieve to obtain the hydrophobic and antifouling coating.

[0028] Example 6 A method for preparing a hydrophobic and antifouling coating includes the following steps: B1. Zinc nitrate hexahydrate, halloysite nanotubes, and deionized water were ultrasonically dispersed in a mass ratio of 600:100:9500. Ammonia was added to adjust the pH to 10. The mixture was heated and reacted at 65°C for 2 hours. After the reaction was completed, the mixture was centrifuged and washed with deionized water and anhydrous ethanol until neutral. It was then vacuum dried in a drying oven at 60°C for 6 hours and calcined in a muffle furnace at 480°C for 2 hours. After cooling, nano-zinc oxide / haloysite nanotube composite filler was obtained. B2. A nano zinc oxide / haloite nanotube composite material with a mass ratio of 100:3500:25, anhydrous ethanol, and γ-methacryloyloxypropyltrimethoxysilane were mixed evenly, heated, stirred and mixed, and the pH was adjusted to 6 with hydrochloric acid solution. The mixture was reacted at 75°C for 12 hours. After the reaction was completed, the mixture was filtered, washed with deionized water and anhydrous ethanol, and dried to obtain an alkenyl-modified composite filler. B3. Deionized water, sodium dodecyl sulfate emulsifier, alkenyl modified composite filler, methyl methacrylate, tridecyl fluorooctyl methacrylate, and vinyltriethoxysilane are stirred and mixed. Ammonium persulfate initiator is added. The mass ratio of deionized water, emulsifier, alkenyl modified composite filler, methyl methacrylate, tridecyl fluorooctyl methacrylate, vinyltriethoxysilane, and initiator is 480:6:12:55:16:7:1. The reaction takes place in a nitrogen atmosphere at a temperature of 75°C for 6 hours. After the reaction is completed, the mixture is cooled and sieved to obtain a hydrophobic and antifouling emulsion. B4. By weight, mix 60 parts of hydrophobic and antifouling emulsion, 2 parts of defoamer, and 0.3 parts of leveling agent at a speed of 500 r / min for 10 min. Add 3 parts of thickener, wherein the defoamer is an organosilicon defoamer, the leveling agent is a polyether-modified polysiloxane, and the thickener is a polyurethane thickener. Stir for 25 min, let stand for 60 min to mature, and sieve to obtain the hydrophobic and antifouling coating.

[0029] Example 7 A method for preparing a hydrophobic and antifouling modified PVC film includes the following steps: Step 1: Perform surface plasma treatment on the modified PVC film with a power of 80W and a treatment time of 5min. Then apply a hydrophobic and antifouling coating to the surface of the treated modified PVC film with a coating thickness of 10μm. Step 2: Place the coated modified PVC film in an oven for three-stage curing. The first stage is cured at 65℃ for 4 minutes, the second stage is cured at 85℃ for 6 minutes, and the third stage is cured at 105℃ for 4 minutes. After cooling, the film is rolled up to obtain a hydrophobic and antifouling modified PVC film.

[0030] The preparation method of the modified PVC film in this embodiment is completely the same as that of the modified PVC film in Example 1, and the preparation method of the hydrophobic and antifouling coating is completely the same as that of the hydrophobic and antifouling coating in Example 4.

[0031] Example 8 A method for preparing a hydrophobic and antifouling modified PVC film includes the following steps: Step 1: Perform surface plasma treatment on the modified PVC film with a power of 90W and a treatment time of 4min. Then apply a hydrophobic and antifouling coating to the surface of the treated modified PVC film with a coating thickness of 14μm. Step 2: Place the coated modified PVC film in an oven for three-stage curing. The first stage is cured at 70℃ for 3 minutes, the second stage is cured at 95℃ for 5 minutes, and the third stage is cured at 110℃ for 3 minutes. After cooling, the film is rolled up to obtain a hydrophobic and antifouling modified PVC film.

[0032] The preparation method of the modified PVC film in this embodiment is completely the same as that in Example 2, and the preparation method of the hydrophobic and antifouling coating is completely the same as that in Example 5.

[0033] Example 9 A method for preparing a hydrophobic and antifouling modified PVC film includes the following steps: Step 1: Perform surface plasma treatment on the modified PVC film with a power of 100W and a treatment time of 3min. Then apply a hydrophobic and antifouling coating to the surface of the treated modified PVC film with a coating thickness of 16μm. Step 2: Place the coated modified PVC film in an oven for three-stage curing. The first stage is cured at 75℃ for 2 minutes, the second stage is cured at 100℃ for 4 minutes, and the third stage is cured at 115℃ for 2 minutes. After cooling, the film is rolled up to obtain a hydrophobic and antifouling modified PVC film.

[0034] The preparation method of the modified PVC film in this embodiment is completely the same as that in Example 3, and the preparation method of the hydrophobic and antifouling coating is completely the same as that in Example 6.

[0035] Comparative Example 1 A PVC film, compared with Example 8, has no surface coating, uses nano-silica to replace the modified silica in an equal amount, and the remaining components and preparation method are completely the same as in Example 8.

[0036] Comparative Example 2 A PVC film, compared to Example 8, has no surface coating and no modified silica added, but the remaining components and preparation method are completely the same as in Example 8.

[0037] Comparative Example 3 A PVC film, compared with Example 8, has a different preparation method for the hydrophobic and antifouling coating. In this comparative example, no alkenyl-modified composite filler was added to the hydrophobic and antifouling emulsion, while the remaining components and preparation method are completely consistent with Example 8.

[0038] Comparative Example 4 A PVC film, compared with Example 8, was not subjected to plasma treatment, but the remaining components and preparation method were completely the same as those of Example 8.

[0039] The PVC films in Examples 7-9 and Comparative Examples 1-4 were subjected to relevant performance tests, as follows: (1) Hydrophobic performance test: Cut a sample with a size of 10cm×10cm, fix the sample with a clamp and place it horizontally on the sample stage. The volume of water droplets is set to 2.0μL. Slowly move the sample stage until the membrane surface contacts the water droplets and then remove it. Use a contact angle meter to measure the contact angle of the membrane surface. Test three times for each group and take the average value. (2) Anti-fouling performance test: Carbon ink, edible oil and dust mixed stains were evenly applied to the film surface and left at room temperature for 24 hours. The film was wiped once with a dust-free damp cloth. Visual rating: Level 1: Severe stain residue, Level 2: Obvious residue, Level 3: Slight residue, Level 4: Basically no residue, Level 5: Completely clean. The test results are shown in Table 1: Table 1 According to the test results in Table 1, the hydrophobic and antifouling modified PVC film prepared in the embodiments of this invention has excellent hydrophobic and antifouling properties, achieving an antifouling level of 5, and stains can be quickly wiped away. Comparative Examples 1 and 2 did not undergo coating treatment, resulting in no coating and significantly reduced antifouling effect, smaller contact angle, and decreased hydrophobicity. Comparative Example 3 did not introduce alkenyl-modified composite fillers, lacking microscopic rough structure support in the coating, resulting in a smaller contact angle and easier contact, wetting, and adsorption of pollutants, leading to a lower antifouling level. Comparative Example 4 did not undergo plasma surface activation treatment, resulting in poorer wettability of the coating and a decrease in overall performance.

[0040] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.

Claims

1. A hydrophobic and antifouling modified PVC film, characterized in that: Including modified PVC film and hydrophobic and antifouling coating; The modified PVC film, by weight, comprises: 100 parts PVC resin, 5-12 parts modified silica, 20-35 parts composite plasticizer, 3-8 parts heat stabilizer, 1-4 parts lubricant, and 1-3 parts antioxidant. The hydrophobic and antifouling coating is obtained by applying a hydrophobic and antifouling paint onto a modified PVC film; The raw materials of the hydrophobic and antifouling coating, by weight, include: 40-60 parts of hydrophobic and antifouling emulsion, 0.5-2 parts of defoamer, 0.1-0.3 parts of leveling agent, and 1-3 parts of thickener.

2. The hydrophobic and antifouling modified PVC film according to claim 1, characterized in that: The modified PVC film is prepared by the following steps: A1. Nano silica, 90wt% ethanol solution, γ-(methacryloyloxy)propyltrimethoxysilane, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane were ultrasonically dispersed evenly. The pH of the solution was adjusted to 5 with glacial acetic acid, and the mixture was heated to allow the reaction to occur. After the reaction was completed, the mixture was centrifuged, washed with anhydrous ethanol, and dried to obtain modified silica. A2. Weigh out the PVC resin, modified silica, composite plasticizer, heat stabilizer, lubricant, and antioxidant by weight, and mix them evenly in a high-speed mixer at a speed of 300-400 r / min for 15-25 min to obtain a mixture. Add the mixture to a twin-screw extruder for melt blending, extrusion granulation, and obtain modified PVC granules. Add the granules to a calender for calendering, cooling and setting to obtain a modified PVC film.

3. The hydrophobic and antifouling modified PVC film according to claim 2, characterized in that: The mass ratio of nano-silica, 90wt% ethanol solution, γ-(methacryloyloxy)propyltrimethoxysilane, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane in A1 is 100:2400-2600:15-21:20-30. The reaction temperature is 75-85℃, and the reaction time is 18-24h.

4. The hydrophobic and antifouling modified PVC film according to claim 2, characterized in that: During the melt blending process in A2, the screw speed is 100-120 r / min, the melt blending temperature is 160-180℃, the melt blending time is 8-10 min, the calendering temperature is 180-200℃, and the calendering thickness is 0.1-0.3 mm.

5. The hydrophobic and antifouling modified PVC film according to claim 1, characterized in that: The preparation method of the hydrophobic and antifouling coating includes the following steps: B1. Zinc nitrate hexahydrate, halloysite nanotubes, and deionized water were ultrasonically dispersed evenly in a mass ratio of 200-600:100:8000-9500. Ammonia was added to adjust the pH to 9-10. The mixture was heated and reacted at 55-65℃ for 2 hours. After the reaction was completed, the mixture was centrifuged and washed with deionized water and anhydrous ethanol until neutral. It was then vacuum dried in a drying oven at 60℃ for 6 hours and calcined in a muffle furnace at 450-480℃ for 2-3 hours. After cooling, the nano-zinc oxide / haloysite nanotube composite filler was obtained. B2. Mix nano zinc oxide / haloite nanotube composite material, anhydrous ethanol, and γ-methacryloyloxypropyltrimethoxysilane in a mass ratio of 100:3200-3500:18-25 until homogeneous. Heat the mixture, stir, adjust the pH to 5-6 with hydrochloric acid solution, and react at 65-75℃ for 12-18 hours. After the reaction is complete, filter the mixture, wash it with deionized water and anhydrous ethanol, and dry it to obtain alkenyl-modified composite filler. B3. Deionized water, emulsifier, alkenyl modified composite filler, methyl methacrylate, tridecyl fluorooctyl methacrylate, and vinyltriethoxysilane are stirred and mixed. An initiator is added, and the reaction takes place in a nitrogen atmosphere. After the reaction is completed, the mixture is cooled and sieved to obtain a hydrophobic and antifouling emulsion. B4. Mix the hydrophobic and antifouling emulsion, defoamer, and leveling agent at a speed of 300-500 r / min for 10-15 min. Add the thickener and stir for 15-25 min. Let it stand and mature for 30-60 min. Sieve to obtain the hydrophobic and antifouling coating.

6. The hydrophobic and antifouling modified PVC film according to claim 5, characterized in that: The mass ratio of deionized water, emulsifier, alkenyl modified composite filler, methyl methacrylate, tridecyl fluorooctyl methacrylate, vinyltriethoxysilane, and initiator in B3 is 450-480:3-6:7-12:35-55:12-16:4-7:0.5-1. The reaction temperature is 70-75℃, and the reaction time is 6-8 hours. The emulsifier is sodium dodecyl sulfate, and the initiator is ammonium persulfate.

7. The hydrophobic and antifouling modified PVC film according to claim 1, characterized in that: The composite plasticizer is composed of dibutyl phthalate and dioctyl phthalate in a mass ratio of 2:3; the heat stabilizer is a calcium-zinc composite heat stabilizer; the lubricant is butyl stearate; the antioxidant is composed of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the defoamer is an organosilicon defoamer; the leveling agent is a polyether-modified polysiloxane; and the thickener is a polyurethane thickener.

8. A method for preparing a hydrophobic and antifouling modified PVC film as described in any one of claims 1-7, characterized in that: Includes the following steps: Step 1: Perform surface plasma treatment on the modified PVC film, and then apply a hydrophobic and antifouling coating to the surface of the treated modified PVC film. Step 2: Place the coated modified PVC film in an oven for curing, cooling, and winding to obtain a hydrophobic and antifouling modified PVC film.

9. The method for preparing a hydrophobic and antifouling modified PVC film according to claim 8, characterized in that: In the plasma treatment process of step one, the treatment power is 80-100W, the treatment time is 3-5min, and the coating thickness is 10-16μm.

10. The method for preparing a hydrophobic and antifouling modified PVC film according to claim 8, characterized in that: In step two, the curing process is a three-stage curing process: the first stage is cured at 65-75℃ for 2-4 minutes, the second stage is cured at 85-100℃ for 4-6 minutes, and the third stage is cured at 105-115℃ for 2-4 minutes.

Citation Information

Patent Citations

  • Oil-resistant adhesive and method of applying the same to prepare oil-resistant, hydrophobic and high-tensile PVC thin film

    CN107502176A

  • Hydrophobic self-cleaning polyvinyl chloride film and preparation method thereof

    CN111777782A

  • Antibacterial PVC film with self-cleaning function

    CN117362864A